Stromersparnis der Zeitumstellung bei privaten Haushalten - Korbinian von Blanckenburg; Julian Strauch (Wirtschaftsdienst, 2016)
Die halbjährliche Zeitumstellung führt immer wieder zu heftigen Diskussionen, ob die damit verbundenen Unannehmlichkeiten durch eine entsprechende Energieersparnis gerechtfertigt sind. Die Autoren haben die Stromersparnis für die Optionen Sommerzeit und Winterzeit (Status quo), nur Winterzeit und nur Sommerzeit berechnet. Sie kommen zu dem überraschenden Ergebnis, dass die höchste Stromersparnis erreicht wird, wenn ausschließlich Sommerzeit gelten würde. – – This paper presents an investigation into the extent to which seasonal time adjustments (summer and winter time) lead to energy savings for private households. The work is based on data from two selected electricity providers in the cities of Kassel and Kempten. By means of a multiple regression model, the electricity utilization of German households was explained with respect to hours of darkness, temperature and global radiation. These variables formed the basis for calculating scenarios with and without seasonal time adjustments. On a comparative basis, summer time throughout the year is associated with the greatest energy savings. We argue that the reason for this is that the highest energy consumption can be observed in the evenings, and continual summer time takes the greatest advantage of the available light of the evening hours.
Keywords: P4; J22; C4; 330; Zeitverwendung; Energieeinsparung; Privater Haushalt; Deutschland